Pension Reform, Financial Market Development, and Economic Growth : Preliminary Evidence From Chile - Holzmann, Robert (Washington, D.C. : International Monetary Fund, 1996)
The Chilean pension reform of 1981, in which Chile moved from an unfunded to a funded scheme, is considered to have contributed to this country's excellent economic performance since the mid-1980s. The paper highlights the theoretical underpinnings of the claimed economic effects and presents empirical data and preliminary econometric testing of the conjectured growth, capital formation, and saving effects. The empirical evidence is consistent with most of the claims. In particular, the direct impact of financial market development on private saving is found to be negative, which underscores the importance of sound fiscal policy and public saving to support the transition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet